The Nitrile‐Forming Enzyme 7‐Cyano‐7‐Deazaguanine Synthase from Geobacillus kaustophilus: A Reverse Nitrilase?. Issue 16 (14th October 2015) - Winkler, Margit; Dokulil, Katharina; Weber, Hansjörg; Pavkov‐Keller, Tea; Wilding, Birgit
Abstract 7‐Cyano‐7‐deazaguanine synthase (E.C. 6.3.4.20) is an enzyme that catalyzes the formation of a nitrile from a carboxylic acid and ammonia at the expense of ATP. The protein from G. kaustophilus was heterologously expressed, and its biochemical characteristics were explored by using a newly developed HPLC‐MS based assay, 31P NMR, and a fluorescence‐based thermal‐shift assay. The protein showed the expected high thermostability, had a pH optimum at pH 9.5, and an apparent temperature optimum at 60 °C. We observed strict substrate specificity of QueC for the natural substrate 7‐carboxy‐7‐deazaguanine, and determined AMP and pyrophosphate as co‐products of preQ0.